Placing Priority on Faith in Providing a Foundation for Children to Face Puberty - Falasifah Ani Yuniarti; Djauhar Ismail; Yayi Suryo Prabandari; Sri Werdati (Universitas Muhammadiyah Yogyakarta, 2021)
Background: Children will experience puberty at the age of 9-15 years, influenced by several factors. Various changes require children to be ready to face them. Teachers carry out preparations, especially those who teach in elementary schools.Objective: This research is qualitative research that aims to explore the preparation made by teachers in preparing for puberty. A total of nine Islamic-based school teachers were interviewed at their schools.Methods: In-depth interviews were conducted using structured open questions. The analysis employed Van Manen’s method.Result: This study raised three themes: the teacher's perception of student development, how the teacher prepares for puberty, and the problems faced in educating children to face puberty.Conclusion: it is necessary to develop a model that can prepare children to enter puberty.